Eﬀect of alkali/mixed alkali metal ions on the thermal and spectralcharacteristics of Dy3+:B2O3-PbO-Al2O3-ZnO glasses - Lakshminarayana, Gandham; Omar Baki, Sharudin; Lira, Alicia; Caldiño, U.; Meza-Rocha, A. N.; Kityk, Iwan V.; Abas, Ahmad Fauzi; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (Elsevier, 2018)
Thermal and spectroscopic features of 50 B2O3–10 PbO–10 Al2O3–10 ZnO–(x) Li2O–(y) Na2O–(z) K2O–1.0 Dy2O3 (mol %) (x = 19, y = 0, and z = 0; x = 0, y = 19, and z = 0; x = 0, y = 0, and z = 19; x = 9.5, y = 9.5, and z = 0; x = 9.5, y = 0, and z = 9.5; x = 0, y = 9.5, and z = 9.5) glasses, that were fabricated by utilizing melt-quenching approach, are investigated by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), optical absorption, photoluminescence excitation (PLE), photoluminescence (PL), and PL decay lifetimes. PL spectra for all the Dy3 +-doped samples show emission bands at 453 nm (blue), 482 nm (blue), 573 nm (yellow), 662 nm (red), and 752 nm (red) corresponding to the 4I15/2 → 6H15/2, 4F9/2 → 6H15/2, 4F9/2 → 6H13/2, 4F9/2 → 6H11/2, and 4F9/2 → 6H9/2 transitions, respectively, upon excitation at 350 nm. Here, Dy3 +: Li–Na glass shows the highest PL intensity for all identified emissions. The yellow-to-blue (Y/B) emission intensity ratio (varied within the range 1.257–1.376), CIE chromaticity coordinates (x,y) (slight variation between (0.3410, 0.3802) and (0.3495, 0.3872), and correlated color temperatures (CCTs) (changed from 4953 K to 5212 K) are calculated following the PL spectra. Dy3 +: 4F9/2 decay curves show non-exponential behavior and are fitted by the Inokuti-Hirayama (I–H) model, where S = 6 shows best fit, indicating dipole-dipole (d-d) interactions for Dy3 + excited (donor) and ground state (acceptor) ions.